Nalp Signalling is Required in Sertoli Cells for Tight-Junction Protein Interaction - Hayrabedyan S. (Sciendo, 2015)
The present study aims to investigate the NALP3 system and its influence on occludin in Sertoli cells, utilising primary murine cells and adult Sertoli cell line as models. Its main goals are the Sertoli cell biology with possible implications on male reproductive functions. Primary and adult Sertoli cells were transfected with NAPL3 siRNA and treated with NOD1 (ie-DAP) and NOD2 (MDP) receptor ligands. There was positive occludin expression levels on transcript (RT-qPCR) and protein (FCS and Immunofluorescence) levels for both cell types. The innate immunity and tight-junction pathways integration serve a protective role for both testis immune barrier and spermatogenesis compartmentalisation maintained by the very same barrier. This integration also points the way for mechanistic research of the disturbances inflicted during an inflammatory response in testis niche.